Análise e desenvolvimento de um microcontrolador didático - Bertuol, Vinicius (2024)
The present work introduces the development of a generic didactic microcontroller, aiming to provide a practical and efficient solution for teaching microcontrollers and digital systems in Computer Engineering. The research highlights the importance of hands-on learning with microcontrollers in the technical training of engineers, aligning with the National Curriculum Guidelines and the current demands of the market. The methodology adopts a practical and progressive approach, introducing fundamental theoretical concepts, followed by practical application through the development of a complete hardware-level microcontroller. The project is structured into stages of research, analysis, planning, implementation, and testing. The implementation employs software tools that enable the modeling, design, and simulation of the hardware components of a microcontroller in a virtual environment, facilitating a deeper understanding of the architecture and operation of these critical computing devices. Computer simulations conducted validated the functionality of the model, emphasizing its adherence to the expected theoretical behavior. This work contributes to the teaching of microcontrollers by proposing an adaptable didactic solution capable of fostering project-based learning and the development of critical skills. Additionally, it reinforces the integration of theory and practice, preparing future engineers for the technological challenges of the market while promoting innovation within the educational environment